Biorefinery of Chlorella sp. using integrated multiphasic systems for biofuel, feed and wound healing application - Koyande, Apurav Krishna (2022)
Microalgae have been explored as a sustainable alternative to fuel and feed on natural resources. Microalgae possess numerous advantages over their renewable counterparts such as soybean and palm oil. It does not compete with agricultural land or freshwater for food crop production, making it a potential biofuel source. However, commercialisation of microalgae biodiesel is yet to make a presence in the billion-dollar biofuel industry due to the bottlenecks. These include rigid microalgae cell wall, low biomass concentration in the harvested culture and high downstream costs. Therefore, a fossil fuel-derived concept of refinery can be introduced to microalgae to overcome as aforementioned challenges.